Mapping Emotional Strength: Building Self-Confidence through Emotional Maturity in Late Adolescent Girls - Putridianti, Balqis (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Many late adolescent girls experience a decline in self-confidence due to social pressure and physical changes during the transition to adulthood. This highlights the importance of emotional maturity in helping individuals recognize, manage, and accept themselves more effectively. This study aims to identify the contribution of emotional maturity to self-confidence in late adolescent girls. A total of 156 female respondents aged 18–22 years living in the Greater Jakarta area were selected using purposive sampling. The data were analyzed using simple linear regression. The results showed that emotional maturity contributed 56.1% to self-confidence, while the remaining 43.9% was influenced by other factors outside this study. These findings confirm that emotional maturity plays a significant role in shaping self-confidence among late adolescent girls.Banyak remaja akhir putri mengalami penurunan kepercayaan diri akibat tekanan sosial dan perubahan fisik yang terjadi selama masa transisi menuju dewasa. Kondisi ini menyoroti pentingnya kematangan emosi dalam membantu individu mengenali, mengelola, dan menerima dirinya dengan lebih baik. Penelitian ini bertujuan untuk mengidentifikasi kontribusi kematangan emosi terhadap kepercayaan diri pada remaja akhir putri. Sebanyak 156 responden berusia 18–22 tahun yang berdomisili di wilayah Jabodetabek dipilih dengan teknik purposive sampling. Data dianalisis menggunakan regresi linear sederhana. Hasil penelitian menunjukkan bahwa kematangan emosi memberikan kontribusi sebesar 56,1% terhadap kepercayaan diri, sementara 43,9% sisanya dipengaruhi oleh faktor lain di luar penelitian ini. Temuan ini menegaskan bahwa kematangan emosi berperan signifikan dalam membentuk kepercayaan diri remaja akhir putri.